SIMULASI REKAYASA LALU LINTAS PADA KAWASAN WISATA KOTA LAMA SEMARANG - Perdana, Haris Athiya; Mudiyono, Rachmat; Adi, Henny Pratiwi (Politeknik Negeri Semarang, 2023)
The Old Town area of Semarang is a tourist area that will be projected as a pedestrian area. The first step starts with the Car Free Night policy. This policy was carried out by closing Jl. Letjen Suprapto as a pedestrian area. The purpose of this study is to determine the performance conditions of the intersections in the Old City Area. Data collection in this study used an intersection inventory survey method which included intersection geometry, speed, and vehicle volume. The analytical method uses the help of the PTV Vissim 2022 Student Version application. Based on PTV Vissim analysis for normal day intersection performance, it was found that the lowest intersection performance occurred at the Letjen Suprapto Intersection with service level F where there was a delay of 80 seconds/vehicle and a queue of 127 m long. During Car Free Night, the lowest intersection performance is shown by level of service D, delay of 38 seconds/vehicle, and queue of 57 m. this condition occurs at the Mpu Tantular Intersection. The Car Free Night policy has had a positive impact on the performance of the traffic flow network in the Old City of Semarang as indicated by the increased level of intersection service.